Peningkatan Keaktifan Dan Hasil Belajar IPS Melalui Model Group Investigation (GI) Pada Siswa Kelas V SDK St. Herman Yoseph Paupire - Petronela Waha Piran (Program Studi Pendidikan Ekonomi, Universitas Flores, 2022)
The purpose of this study is to: increase student activity and learning outcomes in social studies learning material on Natural Appearance and Social Conditions in Neighboring Countries with the GI learning model for fifth grade students at SD Catholic St. Herman Yoseph Paupire Kec. Central Ende Kab. The end of the 2018/2019 school year. The type of research is Classroom Action Research (CAR), with research procedures: planning, action, observation, and reflection. Data collection techniques used: observation, interviews, and tests. The data validity technique uses data/source triangulation and method triangulation. The data analysis technique used descriptive comparative between cycles and descriptive statistics. Based on the results of the study, it was shown that learning through the GI model could increase the activeness and learning outcomes of Social Sciences material on Natural Appearance and Social Conditions of Neighboring Countries. a) The percentage increase in student activity is 23.09% for cycle 1 and 27.31% for cycle 2. b) increasing the percentage of students who achieve the following minimum learning mastery (KKM): in the initial conditions, the percentage of KKM achievement is 33,3 % (8 students), in cycle 1 the percentage increased to 83,33% (20 students), and in cycle 2 the percentage of students who achieved the KKM increased to 100% (24 students).